The creative brain : the science of genius - Andreasen, Nancy C. (Plume, 2006)
"In her tour of creativity and the brain, Nancy Andreasen, professor of psychiatry at the University of Iowa and the winner of the National Medal of Science, shows us that creativity is not the same as intelligence, nor the same as skill. Rather, we discover, the essence of creativity is to shape the materials of life in new and unexpected ways." "Andreasen explores how the human brain achieves creative breakthroughs - in art, literature, music, and science - the role of genes and environment, extraordinary creativity vs. ordinary creativity, the possession of a omnivorous vision, the value of not having a "standard education," and the question of "genius and insanity". The author examines what extraordinary creators such as Mozart, Henri Poincare, and Coleridge, said about creating and how their insights reflect particular qualities of creative people and the creative process. She includes her fascinating interview with the playwright Neil Simon in which he described how his mind and brain work." "Andreasen also shows how her studies of participants in the Iowa Writer's Workshop and other evidence suggest that, while creativity often may be inherited and may sometimes be associated with mental disorders, neither is inevitable or necessary for creativity to flourish." "The Creating Brain offers insight into what creates the creative brain, and offers advice to nurture it in both children and adults."--Jacket